2023
DOI: 10.1051/alr/2023013
|View full text |Cite
|
Sign up to set email alerts
|

Fishmeal replacement by mealworm (Tenebrio molitor) in diet of farmed Pacific white shrimp (Litopenaeus vannamei): effects on growth performance, serum biochemistry, and immune response

Abstract: Reducing the use of fishmeal (FM) in shrimp feed means significant savings in the amount of FM consumed globally and subsequently reducing production costs and environmental impacts. Insect meal (IM) is one of the protein sources to replace FM in aquafeeds. In this regard, this study was conducted with the aim of investigating the effect of replacing FM with mealworm (MW, Tenebrio molitor) on the growth performance, haemolymph biochemical responses, and innate immunity of Litopenaeus vannamei. Shrimps with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Therefore, dueto the quality and quantity of its macronutrients and the presence of carotenoids in TP, the use of an optimal diet based on this by-product can support the production of mealworms and its products (flour and oil), to be used both as foods [121][122][123] and as feed [124][125][126] with high nutritional value and positive effects on human and animal health [59,127]. Great attention must be paid to the origin and traceability of by-products used in diets to avoid accumulating and biomagnifying heavy metals in larvae [128].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dueto the quality and quantity of its macronutrients and the presence of carotenoids in TP, the use of an optimal diet based on this by-product can support the production of mealworms and its products (flour and oil), to be used both as foods [121][122][123] and as feed [124][125][126] with high nutritional value and positive effects on human and animal health [59,127]. Great attention must be paid to the origin and traceability of by-products used in diets to avoid accumulating and biomagnifying heavy metals in larvae [128].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting aspect that has been confirmed in this review is that there is sufficient scientific evidence to assume that the inclusion of TMM to replace FM does not reduce the immune response of crustaceans, but, on the contrary, strengthens it. For instance, the study published by Sharifinia et al (2023) found that replacing FM with TMM up to 30% in the diet of L. vannamei increased the counts of THCs, although this increase was not significant. These findings were those described by Overall, the findings of this paper suggest that TMM is a promising alternative protein source for this shrimp species, as it enhances both growth performance and the immune system, which only contrasts with the results obtained by Li et al (2022), which indicates that TMM was less effective for L. vannamei compared to the control diet (0% of TMM).…”
Section: Effects Of Dietary Tmm On Crustacean´s Immune Responsementioning
confidence: 97%
“…Indeed, Sharifinia et al (2023) concluded that there is strong evidence that TMM can effectively replace FM in the diet of L. vannamei, resulting in enhanced growth of this crustacean. Furthermore, Zheng et al ( 2023) found no decrease in growth performance or feed utilization due to the dietary treatment with TMM proteins.…”
Section: Effects Of Dietary Tmm On Crustacean´s Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 30 years, aquaculture has experienced unprecedented growth, currently accounting for more than half of the world's fish needs and playing a crucial role in food security, income generation, and economic development [ 1 , 2 ]. As a result, aquaculture has emerged as a significant driver of economic growth and poverty reduction in developing countries, with the potential to generate vital income through small-, medium-, and large-scale commercial aquaculture [ 3 5 ]. However, to meet the growing demand for safe and high-quality aquatic protein, especially fish and shrimp, aquaculture requires appropriate production systems capable of sustaining higher stocking densities, maintaining acceptable water quality levels, ensuring optimal health and performance, while addressing biosecurity and environmental concerns [ 6 ].…”
Section: Introductionmentioning
confidence: 99%